A note on the Baltic future participle - Villanueva Svensson, Miguel (Baltistica, 2012)
The lack of fit between the finite forms (Lith. 3 duõs, 1 pl. dúosime, etc.) and the participle (Lith. dúosiant-, cf. Sl. byšǫšt-) of the Baltic future (going back to two PIE desiderative types: athematic and *‑se/o‑) can be explained as follows: since the future participle is a form of very modest occurrence, it could be generalized from some verbs with an inherited se/o‑desiderative („to be“, „to come“, „to die“, etc.) whose participle was of relatively frequent use.